The role of the Anti-Bullying Task Force In Minimizing (Verbal) Violence In The Private Ibtidaiyah Madrasah Imam Syafi'i, Telaga District, Gorontalo Regency - Polihito, Rahmat; Panai, Abdul Haris; Pongoliu, Yusraningsih H. (Advances In Social Humanities Research, 2024)
The aim of this study was to assess the effectiveness of the Anti-Bullying Task Force in reducing verbal violence at Private Ibtidaiyah Madrasah Imam Syafi'I, Telaga District, Gorontalo Regency. Utilizing a Descriptive Approach with a qualitative research type, the study employed stratified random sampling to select 9 respondents. Data collection methods included observation, interviews, and documentation. The task force primarily focused on prevention through various strategies, such as providing advice during morning dhikr sessions and before learning activities, as well as educating students on the consequences of bullying. In handling incidents, the task force employed motivational counseling and imposed sanctions when necessary, ensuring student agreement and avoiding physical harm. Post-traumatic support emphasizes providing encouragement to victims of verbal violence, encouraging them to respond assertively without resorting to physical confrontation. The study revealed that gentle counseling had a positive impact, as evidenced by increased reporting of bullying incidents and a reduction in bullying behaviors within the madrasah. Overall, the findings underscored the importance of proactive intervention and supportive measures in mitigating verbal violence among students.